Children's Multilingual Development and Education : fostering linguistic resources in home and school contexts - Bailey, Alison L.; Osipova, Anna V. (New York [etc.] Cambridge University Press, 2015)
The study of families and educators who successfully sustain children's linguistic resources is a novelty in current educational research, where focus has largely been on the development of students'English language skills. In this book, Alison L. Bailey and Anna V. Osipova provide a systematic examination of the beliefs and practices of parents and educators who share the common goal of improving educational and social outcomes for multilingual children. Giving voice to parents and educators, they explore the strategies being devised to foster multilingualism and support its development both at home and in the classroom. This book presents new research findings and combines these with compelling firsthand accounts of the successes and concerns of both families and educators, making its content pertinent to a wide audience of researchers and a range of higher education courses.
Keywords: Bilinguismo en niños; Libros electrónicos